2006
DOI: 10.1002/adfm.200600141
|View full text |Cite
|
Sign up to set email alerts
|

On the Origin of Green Emission Bands in Fluorene‐Based Conjugated Polymers

Abstract: Blue‐light‐emitting diodes made of polyfluorenes have low stability and, under operation, rapidly degrade and produce undesirable low‐energy emission bands (green or g‐bands). A spectroelectrochemical study of the degradation process suffered by polyfluorenes is reported here. These polymers lose their electronic properties by electrochemical oxidation and reduction through σ‐bond breaking. In addition, upon electrochemical reduction, the development of a structured green emission band at 485 nm is observed. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
94
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(98 citation statements)
references
References 26 publications
3
94
1
Order By: Relevance
“…For LED A (PFO/ZnO) it showed an emission peaks at 455 nm, 470 nm, and extended peaks with a two features at 510 nm and 540nm, the first two blue peaks correspond to the PFO as discussed above [28]. The first green peak appeared at 510 nm, this peak has recently been studied by R. Mallavia et al and they have shown that upon electron injection the PF polymers electrochemically degraded leading to the formation of new species and cross-linking of the polymer chains [29]. The band at about 540 nm has two possible sources, the oxygen vacancies V O in ZnO which is frequently observed in low temperature grown ZnO NRs , or due to the recombination of electrons with interface states in PFO/ZnO [30].…”
mentioning
confidence: 99%
“…For LED A (PFO/ZnO) it showed an emission peaks at 455 nm, 470 nm, and extended peaks with a two features at 510 nm and 540nm, the first two blue peaks correspond to the PFO as discussed above [28]. The first green peak appeared at 510 nm, this peak has recently been studied by R. Mallavia et al and they have shown that upon electron injection the PF polymers electrochemically degraded leading to the formation of new species and cross-linking of the polymer chains [29]. The band at about 540 nm has two possible sources, the oxygen vacancies V O in ZnO which is frequently observed in low temperature grown ZnO NRs , or due to the recombination of electrons with interface states in PFO/ZnO [30].…”
mentioning
confidence: 99%
“…at a slightly lower wavelength than the usual green band (500-600 nm), can be observed (43,(46)(47)(48)(49) This emission band has previously been assigned to excimer emission in fresh PFs synthesized by Ni-catalysed Yamamoto coupling (19) and it can be observed also in uncapped PFs prepared by Suzuki coupling (11). The formation of intramolecular excimers with the new C-C bonds formed (38), electric field-induced excimer (48) and fluorenone defects introduced by the cathode (43) also would produce a green emission around 485 nm. In our experiments, the BFLBBFLYQ film was spin-coated in air, then it was baked at 100°C for 10 min in air, which would induce the formation of fluorenone defects upon thermal or photo-oxidation in the presence of oxygen (19,43,(50)(51)(52) Therefore, the peak at 452 originates from the emitter of the BFLBBFLYQ molecule, and the peaks of 490, 528 and 576 nm can be attributed to fluorenone defects.…”
Section: Resultsmentioning
confidence: 89%
“…The origin of these emission features has been the subject of hot discussion. Fourier transform infrared (FTIR) spectroscopy has revealed that fluorenone defects, formed on degradation of PFs, are related to the intensity of the low-energy emission band (15,19,(31)(32)(33)(34)(35)(36)(37)(38). The idea that fluorenones could be responsible for the green light emission was substantiated by the synthesis of poly-and oligofluorenes containing a precise number of fluorenone moieties that exhibit green emission, even in dilute solution (24,33,(39)(40)(41).…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…1) and fluorene-arylene copolymers have been studied intensively because of its applications in the LEDs due to their highly efficient blue photoluminescence. (Mallavia et al, 2005) Although the bulk electronic and optical properties of PFO have been studied extensively by UVvisible absorption, Raman, and photoluminescence spectroscopy, (Ariu et al, 2000;Montilla & Mallavia, 2007) the optical and electronic properties of PFO at the buried electrode interface remain unexplored. Because the electronic properties of electrode/organic interface affect the performance of the organic LEDs, understanding of the interaction between the electrode and organic molecules and the electronic structures at the buried interfaces are quite important.…”
Section: Dr-sfg Study Of Poly(99-dioctylfluorene) Surfaces and Al/limentioning
confidence: 99%